A modification method for increasing soluble dietary fiber in corn stalks
Through the method of alkaline hydrogen peroxide pretreatment and combined fermentation of Aspergillus niger-cellulase, the content and functional characteristics of soluble dietary fiber in corn stalks were improved, and the problem of low SDF content in corn stalks was solved, and its food content was realized and efficient application in feed additives.
Patent Information
- Application Number
- CN202310270271.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2043-03-20
AI Technical Summary
The content of soluble dietary fiber (SDF) in corn stalks is low, and its functional characteristics are low, making it difficult to effectively develop and utilize.
The complex structure of corn stalk was broken through alkaline hydrogen peroxide pretreatment, and then the bacterial + enzyme fermentation was performed using Aspergillus niger spore liquid and cellulase to improve the content and functional characteristics of SDF.
It significantly improves the content and physical and chemical properties of soluble dietary fiber in corn stalks, and enhances its application value in food and feed additives.
Smart Images

Figure CN116369433B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biological feed, and particularly relates to a modification method for increasing soluble dietary fiber in corn stalks. Background Art
[0002] Dietary fiber (DF) refers to edible carbohydrates that can resist hydrolysis by digestive enzymes in the small intestine, mainly from crops such as fruits, vegetables, and grains. According to the water solubility of DF, it can be divided into soluble dietary fiber (SDF) and insoluble dietary fiber (IDF). DF has physical and chemical properties such as water holding capacity, oil holding capacity, adsorption, fermentability, and antioxidant properties. These physical and chemical properties play a vital role in human health. According to relevant research reports, DF can improve the structure of intestinal flora, maintain gastrointestinal function, and prevent cardiovascular diseases and diabetes. Epidemiological and animal experiments have shown that DF's adsorption of cholesterol and carcinogens can delay the increase of blood sugar and blood lipids after meals and reduce the incidence of rectal cancer and colon cancer. However, due to the high content of IDF in natural DF, the ratio of SDF to IDF is seriously unbalanced, which significantly reduces the functional characteristics and taste of DF, thereby reducing people's desire for DF. IDF mainly increases the satiety of animals, absorbs fat, promotes intestinal peristalsis, thereby promoting animal defecation and reducing the accumulation of toxins in the body. SDF has good physical and chemical properties such as water holding capacity, adsorption, and swelling, and has high antioxidant capacity. SDF plays an important regulatory role in the balance and health of the intestinal microecology of the body, improves the structure of intestinal microbial flora, promotes the growth of beneficial bacteria, and reduces the reproduction of harmful bacteria. Many of the beneficial effects attributed to dietary fiber are related to SDF. SDF is not only favored for its nutritional value, but also for its superior biological activity and physicochemical properties. However, in the DF composition of most plants, the SDF content is extremely low. Therefore, researchers use modification treatment to increase the SDF content and improve its functional properties.
[0003] "People and animals compete for food" is one of the problems of food security in my country. Effectively solving the problem of feed grain required for the breeding industry is one of the directions for the development of the feed industry in the future. my country's straw resources are diverse, with large output and wide distribution. The rational use of straw resources will bring more social and ecological benefits. At present, my country faces the dual problems of food shortage and waste of abundant lignocellulose resources. Therefore, in order to further make full use of straw resources, this study discusses the modification of corn straw dietary fiber. Corn straw is rich in carbohydrates such as cellulose, hemicellulose and lignin, and is a cheap and easily available source of DF. IDF content is rich in corn straw, but SDF content is low, and its functional properties are low. Therefore, it is necessary to modify corn straw to increase the content of SDF. However, in corn straw, lignin surrounds hemicellulose and cellulose to form a complex structure, and the cellulose binding site is difficult to expose, which makes it difficult to develop and utilize straw resources. Studies have shown that alkaline hydrogen peroxide can destroy lignin and hemicellulose, thereby breaking the tough and complex structure of straw. Therefore, the SDF content can be increased by pretreating corn straw with alkaline hydrogen peroxide to break up its complex structure and then treating the corn straw with biological methods. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a modification method for improving the soluble dietary fiber in corn stalks. The soluble dietary fiber extracted by the modification treatment by this method is significantly improved in terms of water holding capacity, swelling capacity, solubility, DPPH free radical scavenging capacity and cholesterol adsorption capacity, indicating that it has higher physical and chemical properties and biological functional properties, and can be extracted for food and feed additives to reduce cholesterol and resist oxidation.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A modification method for increasing soluble dietary fiber in corn stalks comprises the following steps:
[0007] (1) drying the corn stalks and crushing them into 20-40 mesh;
[0008] (2) placing the crushed corn stalks in an autoclave, and then adding NaOH and water for high pressure treatment;
[0009] (3) After the high pressure treatment, the corn stalks are cooled, treated with H2O2, and air-dried to obtain corn stalks treated with alkali high pressure oxidation;
[0010] (4) adding Aspergillus niger spore liquid and cellulase to the corn stover after alkaline high pressure oxidation treatment to carry out bacteria + enzyme combined fermentation;
[0011] (5) The fermentation broth obtained in step (4) is subjected to an enzyme-weight method to obtain soluble dietary fiber.
[0012] Furthermore, in the step (2), the amount of NaOH added is 8% based on the weight of the crushed corn stalks.
[0013] Furthermore, the liquid-to-solid ratio of the high pressure treatment in step (2) is 2:1 (the liquid-to-solid ratio here is the mass ratio of liquid to solid).
[0014] Furthermore, in step (2), the high pressure treatment temperature is 121° C., the high pressure treatment pressure is 0.1 MPa, and the time is 40 min.
[0015] Furthermore, the amount of H2O2 added in step (3) is 6%.
[0016] Furthermore, in step (4), spores of Aspergillus niger (A. niger) are added in a ratio of 1:1 (w:v), that is, 1 mL of Aspergillus niger spores is added to 1 g of corn stalks after alkaline high pressure oxidation treatment; the amount of Aspergillus niger added is 1×10 7 CFU / mL, the amount of cellulase added was 10FPU / g, the final liquid-to-solid ratio was 2:1 (the liquid-to-solid ratio here is the mass ratio of liquid to solid), pH value was 5.5, and cultured at 30°C for 5 days.
[0017] Furthermore, the operation method of the enzyme-gravimetric method in step (5) is as follows: 0.5 g of sample is added to 5 mL of acetic acid-sodium acetate buffer, and then the sample is added to an α-amylase solution, a protease solution and an amyloamylase solution in sequence, each at 60° C. for 30 min. The final enzymatic hydrolyzate is filtered, and the filtrate is precipitated with 95% ethanol. The precipitate is centrifuged at 10,000×g for 10 min and dried at 65° C.
[0018] Beneficial effects of the present invention: The present invention uses crop waste corn stalks as raw materials, adopts physical-chemical combined pretreatment, and then the soluble dietary fiber content in the stalks reaches 17.49% after Aspergillus niger-cellulase composite fermentation, which is increased by 550%. The process uses biosafety reagents NaOH and H2O2 as treatment reagents and is supplemented by high temperature and high pressure physical methods to break the complex hydrogen bond structure between lignin and hemicellulose, so that cellulose is exposed and swelled, and more binding sites are provided for bacteria-enzyme fermentation, and cellulose and hemicellulose are further degraded into short-chain oligosaccharides, thereby increasing the content of soluble dietary fiber. Through single and multiple combined treatment comparative analysis, it is obtained that the combined fermentation treatment of corn stalks with alkaline high pressure oxidation treatment + Aspergillus niger + cellulase (10FPU / g) is the best. Under the optimal treatment conditions, the soluble dietary fiber content in the stalks is 17.49%. SEM was used to analyze the morphology of soluble dietary fibers obtained by different methods, and the physicochemical and functional properties of soluble dietary fibers obtained by different methods were evaluated by water holding capacity, oil holding capacity, swelling capacity, solubility, DPPH scavenging capacity and cholesterol adsorption capacity. The above experiments show that the soluble dietary fiber obtained by the best modification treatment method has the best performance in water holding capacity, swelling capacity, solubility, DPPH scavenging capacity and cholesterol adsorption capacity. Good functional properties can provide better physiological functions and can be used as food or feed additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Response surface plot of the interaction effect of various factors on SDF extraction rate.
[0020] Figure 2 SEM (5000×) of SDF obtained after different treatment methods. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0022] Cellulase was purchased from Shandong Xiasheng Biotechnology Co., Ltd. The cellulase activity was 347.2 FPU / g. Aspergillus niger (A. niger) (3758) and Trichoderma longifolia (T. longifolia) (3.534) were both from Henan Delin Biotechnology Co., Ltd.
[0023] Example 1
[0024] The method for increasing the soluble dietary fiber in corn stalks in this embodiment comprises the following steps:
[0025] (1) drying the corn stalks and crushing them into 20-40 mesh;
[0026] (2) placing the crushed corn stalks in an autoclave, and then adding NaOH and water for high pressure treatment, specifically, the amount of NaOH added is 8% based on the dry weight (w / w) of the corn stalks, and dissolved in a corresponding volume of distilled water, the prepared NaOH solution is poured into a conical flask containing the corn stalks at a liquid-to-solid ratio of 2:1, and sealed with tin foil, and the conical flask is placed in an autoclave at 121° C. and 0.1 MPa for 40 min;
[0027] (3) After the high pressure treatment, the corn stalks were cooled, treated with H2O2, and air-dried to obtain corn stalks treated with alkali high pressure oxidation, and treated with 6% H2O2 (v / v) for 4 h;
[0028] (4) Adding Aspergillus niger spore liquid and cellulase to the corn stover after alkaline high pressure oxidation treatment for bacteria + enzyme combined fermentation, specifically, adding Aspergillus niger (A. niger) spore liquid in a ratio of 1:1 (w:v) and mixing, the amount of Aspergillus niger added is 1×10 7 CFU / mL, the amount of cellulase added was 10FPU / g, the final liquid-solid ratio was 2:1 (the liquid-solid ratio here is the mass ratio of liquid to solid), pH value was 5.5, and cultured at 30°C for 5 days;
[0029] (5) The fermentation broth obtained in step (4) is subjected to an enzyme-gravimetric method to obtain soluble dietary fiber, and the operation method is as follows: 0.5 g of the sample is added to 5 mL of acetic acid-sodium acetate buffer, and then the sample is sequentially added to an α-amylase solution, a protease solution, and an amyloamylase solution, respectively, at 60° C. for 30 min. The final enzymatic hydrolyzate is filtered, and the filtrate is precipitated with 95% ethanol. The precipitate is centrifuged at 10,000×g for 10 min and dried at 65° C.
[0030] 1. Optimal Experimental Design
[0031] Design-Expert 10 software was used for experimental design. Model fitting, statistical data analysis and Box-Behnken design were applied. According to the pretreatment results of the previous single-factor experiment, the optimal parameters of NaOH addition, high pressure time, liquid-to-solid ratio and H2O2 addition were selected and listed in Table 1 for RSM design. The process of straw alkali high pressure oxidation pretreatment is as follows: (1) Weigh 10g of corn straw and put it into a 250mL conical flask. (2) Calculate the amount of NaOH added (6%, 7%, 8%) according to the dry weight (w / w) of corn straw and dissolve it in the corresponding volume of distilled water. (3) Pour the prepared NaOH solutions of different concentrations into the conical flask containing corn straw at a liquid-to-solid ratio of 2:1, 4:1 and 6:1, respectively, and seal it with tin foil. (4) Put the conical flask into an autoclave at 121℃ and 0.1MPa for 20min, 30min and 40min. (5) After the high pressure is completed, cool to room temperature, add 2%, 4% and 6% H2O2 (v / v) in a conical flask and treat for 4 hours. (6) Place in a 65°C oven for drying, and then perform RSM analysis.
[0032] To relate the relationship between the variables and the response, a quadratic polynomial equation is used for fitting. The general form of the prediction polynomial quadratic equation is as follows:
[0033] Y=β0+β1X1+β2X2+β3X3+β4X4+β 11 X1 2 +β 22 X2 2 +β 33 X3 2 +β 44 X 2 4+β 12 X1X2+β 13 X1X3+
[0034] β 14 X1X4+β 23 X2X3+β 24 X2X4+β 34 X3X4
[0035] Y is the extraction rate of SDF after alkali high pressure oxidation treatment (%); X1, X2, X3, X4 are the independent variables corresponding to the amount of NaOH added, high pressure time, liquid-to-solid ratio and H2O2 added, respectively; β0 is the intercept; β1, β2, β3, β4 are the linear coefficients; β 11 , β 22 , β 33 , β 44 is the square coefficient; β 12 ,β 13 ,β 14 ,β 23,β 24 ,β 34 is the cross-product coefficient.
[0036] Table 1 Design variable levels
[0037]
[0038] 2. Single factor study on the effects of NaOH addition, high pressure time, liquid-solid ratio and H2O2 addition on the SDF extraction rate of corn straw
[0039] 1. Effect of different NaOH addition amounts on SDF extraction rate
[0040] Corn straw was modified under the conditions of high pressure time of 30 min, liquid-to-solid ratio of 6:1, H2O2 addition of 4%, and NaOH addition of 0%, 3%, 4%, 5%, 6%, and 7%. The effect of different NaOH addition amounts on the SDF extraction rate of corn straw was explored. The results are shown in Table 2.
[0041] Table 2 Effect of different NaOH addition amounts on SDF extraction rate
[0042]
[0043]
[0044] Note: Data are expressed as mean ± standard deviation (n = 3). Different lowercase letters in the same column indicate significant differences (p < 0.05), and the same letters indicate insignificant differences (p > 0.05). The same below.
[0045] It can be found from Table 2 that the content of IDF decreases with the increase of NaOH addition. When the NaOH addition amount is 7%, the extraction rate of SDF is significantly higher than that of other groups (p<0.05).
[0046] 2. Effect of different high pressure time on SDF extraction rate
[0047] With a liquid-to-solid ratio of 6:1, an H2O2 addition amount of 4%, and the NaOH addition amount determined in the above experiment, corn straw was modified under the conditions of 0 min, 10 min, 20 min, 30 min, 40 min, and 50 min, respectively, to explore the effect of high pressure time on the SDF extraction rate. The results are shown in Table 3.
[0048] Table 3 Effect of different high pressure time on SDF extraction rate
[0049]
[0050] It can be seen from Table 3 that when the high pressure time is 50 minutes, the SDF extraction rate reaches the highest, but there is no difference in the SDF extraction rate between the high pressure time of 30 minutes and 50 minutes (p>0.05), so the high pressure time is determined to be 30 minutes.
[0051] 3. Effect of different liquid-solid ratios on SDF extraction rate
[0052] With an H2O2 addition amount of 4%, the NaOH addition amount and high pressure time determined in the above experiment, corn straw was modified at liquid-solid ratios of 2:1, 4:1, 6:1, 8:1, and 10:1, respectively, to explore the effect of liquid-solid ratio on SDF extraction rate. The results are shown in Table 4.
[0053] Table 4 Effect of different liquid-solid ratios on SDF extraction rate
[0054]
[0055] Table 4 shows the effect of different liquid-solid ratios on the SDF extraction rate. There is no difference in the IDF content of different liquid-solid ratios (p>0.05), indicating that the liquid-solid ratio has no significant effect on the IDF content. There is no significant difference in the SDF extraction rate between the liquid-solid ratio of 4:1 and 8:1 (p>0.05), so the liquid-solid ratio was determined to be 4:1.
[0056] 4. Effect of different H2O2 addition amounts on SDF extraction rate
[0057] With the NaOH addition amount, high pressure time and liquid-to-solid ratio determined in the above experiment, corn straw was modified at 0%, 2%, 4%, 6% and 8% conditions respectively, and the effect of H2O2 addition amount on SDF extraction rate was investigated. The results are shown in Table 5.
[0058] Table 5 Effect of different H2O2 addition amounts on SDF extraction rate
[0059]
[0060] It can be seen from Table 5 that the addition of H2O2 has a certain effect on improving the SDF extraction rate, but there is no difference in the SDF extraction rate when the H2O2 addition amount is 4% and 8%, so the H2O2 addition amount is determined to be 4%.
[0061] In summary, the amount of NaOH added, high pressure time, liquid-to-solid ratio and H2O2 added were determined to be 7%, 30 min, 4:1 and 4% respectively.
[0062] 3. Response Surface Optimization of Alkaline High Pressure Oxidation Conditions
[0063] The experimental values and predicted values of 29 runs were shown in Table 6 using the Box-Behnken design of Design Expert 8.0.5 software. Each response result is the average of three repeated experiments. A response surface regression model was established, and regression analysis of variance (ANOVA) was performed to estimate the effects of the variables and their possible interactions. The results of the ANOVA of the adjusted model are shown in Table 7. The regression model equation is as follows:
[0064] Y=+8.91+0.62X1+0.054X2+0.65X3+0.34X4+0.47X1X2-0.24X1X3-0.017X1X4-0.2
[0065] 5X2X3+0.30X2X4-0.36X3X4+1.05X1 2 -0.39X2 2 +0.12X3 2 -0.074X4 2
[0066] In this response surface design experiment, it was found (Table 7) that the SDF regression model P < 0.0001, indicating that the regression model is statistically significant. In this regression model, the amount of NaOH added X1 (P < 0.0001), liquid-solid ratio X3 (P < 0.0001), H2O2 addition X4 (P = 0.0056), X1 2 (P<0.0001) and X2 2 The P values in (P=0.0156) are all less than 0.05, indicating that these factors have a significant effect on the SDF extraction rate. The P value in X1X2 (P=0.0225) is less than 0.05, indicating that there is an interaction between X1 and X2. The P value of the lack of fit term of the model is 0.8035, which is greater than 0.05, that is, the lack of fit of the regression equation model is not significant, indicating that the equation has a good fit. The coefficient of determination R of the regression model 2 The value is 0.9253 and the corrected R 2 The value is 0.8507, which is greater than 0.85, indicating that the regression equation has a good fit and a high accuracy of the predicted value. The CV (%) of the regression equation is 3.96, which is less than 10, reflecting the stability and effectiveness of the response surface design experiment.
[0067] With the help of RSM analysis, the optimal alkaline oxidation high pressure treatment conditions predicted in this study were 8% NaOH addition, 40 min high pressure time, 2:1 liquid-solid ratio and 6% H2O2 addition. The estimated SDF extraction rate was 11.589%. After three repeated tests, the SDF extraction rate was 11.32%, which proved the effectiveness of the response surface. The three-dimensional (3D) response surface diagram is shown in Figure 2. Figure 1As shown, the interaction between the two variables is displayed and the optimal level is determined.
[0068] Table 6 Response surface experimental design and results of SDF extraction process parameters
[0069]
[0070] Table 7 Results of variance analysis of regression model for SDF extraction process
[0071]
[0072] Note: Significance at*p<0.05 **p<0.01
[0073] 4. Effects of different treatment methods on the extraction rates of IDF, SDF and SDF / IDF in corn straw
[0074] Corn stover was pretreated by alkaline high pressure oxidation. Subsequently, unmodified DF (U-DF) and DF treated by alkaline high pressure oxidation (A-DF) were subjected to the following three treatment methods: enzymatic hydrolysis, fermentation, and bacterial-enzyme complex fermentation.
[0075] Enzymatic hydrolysis: Add 5% (w / v) distilled water and 15 FPU / g cellulase to the straw, react at 180 rpm in a shaking incubator at 50°C for 2 h, and then inactivate the enzyme at 100°C for 30 min.
[0076] Bacterial fermentation method: The pH value of the straw was adjusted to 5.5 and sterilized by high pressure. The spores of Aspergillus niger or Trichoderma longifolia (1×10 7 CFU / mL) was mixed. The final liquid-to-solid ratio was 2:1 and cultured at 30°C for 5 days.
[0077] Bacteria-enzyme complex fermentation method: The pH value of the straw was adjusted to 5.5 and sterilized by high pressure. The spores of Aspergillus niger or Trichoderma longifolia (1×10 7 CFU / mL) and 15 FPU / g cellulase were mixed. The final liquid-to-solid ratio was 2:1. The experiment was performed in triplicate and cultured at 30°C for 5 days.
[0078] The trials were divided into the following groups:
[0079] Group 1: U-DF + Cellulase
[0080] Group 2:U-DF+A.niger
[0081] Group 3: U-DF+A.niger+cellulase
[0082] Group 4: U-DF+T.longifolia
[0083] Group 5: U-DF+T.longifolia+cellulase
[0084] Group 6: A-DF + Cellulase
[0085] Group 7:A-DF+A.niger
[0086] Group 8: A-DF+A.niger+cellulase
[0087] Group 9: A-DF+T.longifolia
[0088] Group 10: A-DF+T.longifolia+cellulase
[0089] 5. Discussion on different enzyme amounts in Aspergillus niger-enzyme complex fermentation
[0090] Solid-state fermentation was carried out in a 100 mL cotton-stoppered Erlenmeyer flask. The pH of the straw was adjusted to 5.5 and sterilized by autoclaving. 5 g of straw was mixed with 5 mL of A. niger (5 × 10 7 CFU / mL) and 5, 10 and 15 FPU / g cellulase liquid cultures were mixed. The final liquid-to-solid ratio was 2:1 and cultured at 30°C for 5 days.
[0091] Group 1: A-DF+A.niger+5FPU / g cellulase
[0092] Group 2: A-DF+A.niger+10FPU / g cellulase
[0093] Group 3: A-DF+A.niger+15FPU / g cellulase
[0094] Extraction of SDF: SDF was obtained by enzyme-gravimetric method. 0.5 g of sample was added to 5 mL of acetic acid-sodium acetate (HAc-NaAc) buffer. The sample was then added to a-amylase solution, protease solution and amyloamylase solution in sequence at 60°C for 30 min. The final enzymatic hydrolysate was filtered and the filtrate was precipitated with 95% ethanol (1:4 v / v). The precipitate was centrifuged at 10,000 × g for 10 min and dried at 65°C.
[0095]
[0096] Where Ms is the weight of SDF and Mr is the weight of raw material.
[0097] Table 8. Effects of different treatments on the extraction rates of IDF, SDF and SDF / IDF from corn straw
[0098]
[0099] From the SDF extraction rate in Table 8, it can be seen that the SDF extraction rate of the A-DF+A.niger+cellulase group was the highest (17.15%), which was 550% higher than that of the U-DF group (2.64%). The next highest was A-DF+A.niger (12.15%) and A-DF (11.32%), but the difference between the two groups was not significant (p>0.05).
[0100] The A-DF obtained by alkaline high-pressure oxidation pretreatment, the combined action of H2O2 and NaOH can destroy lignin and change the structure of hemicellulose and cellulose, making some non-starch polysaccharides easier to dissolve, thereby improving the extraction rate of SDF.
[0101] The SDF extraction rate of U-DF and A-DF fermented by A. niger + cellulase was significantly higher than that of A. niger fermented (p<0.05%). Therefore, the combined action of A. niger and cellulase can improve the SDF extraction rate in corn straw.
[0102] The results of cellulase hydrolysis of U-DF showed that the SDF extraction rate increased, which may be caused by the hydrolysis of cellulose by cellulase; however, the hydrolysis of A-DF showed the opposite result. It is speculated that the lignin in A-DF was destroyed and the cellulose was degraded into polysaccharide molecules after alkali high-pressure oxidation treatment. These polysaccharide molecules are more easily hydrolyzed, thus reducing the SDF extraction rate.
[0103] T. longifolia fermentation increased the SDF extraction rate in U-DF, but reduced the SDF extraction rate in A-DF. The SDF extraction rate of T. longifolia + cellulase combined fermentation was lower than that of T. longifolia fermentation, indicating that SDF was consumed in this fermentation system. Therefore, using A. niger + cellulase to ferment A-DF is the best way to increase the SDF extraction rate.
[0104] Table 9. Effects of different cellulase addition amounts on the IDF, SDF and SDF / IDF extraction rates of corn straw fermented with A. niger + cellulase
[0105]
[0106] Table 9 shows that with the increase of cellulase addition, the extraction of SDF first increased and then decreased. When the cellulase addition amount was 10FPU / g, the extraction rate of SDF reached the maximum (17.49%). Compared with U-DF, the extraction rate of SDF increased by 563%. Therefore, the extraction rate of A. niger (5×10 7 CFU / g)+cellulase (10FPU / g) fermentation of A-DF is the best process to improve the SDF extraction rate.
[0107] 6. Index detection
[0108] 1. Scanning electron microscope (SEM) morphology analysis
[0109] The surface and microstructure were observed by scanning electron microscopy (FEI Q45 environmental scanning electron microscope, Czech Republic) at 20 kV. The powder samples were mounted on a metal holder and coated with 10 nm layers of gold and palladium by ion sputtering. Each sample was photographed at a magnification of 5000 times, as shown in Figure 2. Figure 2 As shown. Figure 2 It can be seen that the surface of U-SDF is flat and smooth, without obvious pore structure, and is similar to a stone block. A-SDF has many pores of different sizes on the surface and also presents a block state. F-SDF shows a completely different state. It is granular and loose with irregular distribution, indicating that the macromolecular glycosidic bonds between the long chains of cellulose are effectively destroyed through fermentation, which increases the specific surface area of SDF. The microstructure of F-SDF is closely related to its physical and chemical properties and functional properties.
[0110] 2. Physical and chemical properties
[0111] 1) Water Holding Capacity (WHC)
[0112] 0.20 g SDF and 10 mL distilled water (4 mL) were placed in a centrifuge tube and sealed, shaken at 180 rpm in an oscillating tank at 37 ° C for 12 h, and then centrifuged at 10000 r / min for 10 min, the supernatant was removed, and the weight of the wet sample and the centrifuge tube was recorded (M1). Finally, the hydrated residue was dried at 105 ° C to a constant weight. The weight of the dry sample and the centrifuge tube was recorded (M2), and the dry sample (M3) was recorded. WHC was calculated by the following formula:
[0113] WHC(g / g)=(M1-M2) / M3
[0114] Where M1 is the weight of the wet sample and the centrifuge tube, M2 is the total weight of the dry sample and the centrifuge tube, and M3 is the weight of the dry sample.
[0115] 2) Oil holding capacity (OHC)
[0116] The OHC determination method is to mix 10mL peanut oil (4mL peanut oil) with 0.20g SDF (M1) at 37℃ for 12h, centrifuge at 10000r / min for 10min, collect the precipitate and weigh it (M2). The OHC calculation method is as follows:
[0117] OHC(g / g)=(M2-M1) / M1
[0118] Where M1 is the weight of the sample and peanut oil, and M2 is the total weight of the sample.
[0119] Studies have shown that the water holding capacity of DF helps increase excretion and promote normal intestinal peristalsis. Water holding capacity can improve the viscosity of SDF to a certain extent. High-viscosity SDF has better adhesion and can prevent intestinal epithelial cells from absorbing harmful substances. In food, high-viscosity SDF can be used as a gelling agent, thickener, stabilizer, etc. to improve the texture of food. As shown in Table 10, the water holding capacity of F-SDF is significantly higher than that of A-SDF and U-SDF, while U-SDF has the lowest water holding capacity (p<0.05). The oil holding capacity of F-SDF is significantly higher than that of U-SDF and lower than that of A-SDF (p<0.05). F-SDF has good water holding capacity. It may be that during the fermentation process, the macromolecular glycosidic bonds are broken, which increases the specific surface area of SDF and exposes more hydrophilic groups, which is related to the morphological structure of F-SDF.
[0120] 3) Swelling capacity (SWC)
[0121] SWC is to put 0.1g sample (M) into a 25mL graduated tube and record its volume (V1). Then add distilled water (5mL), place it in a 37℃ incubator for 12h, and finally record the expanded volume (V2).
[0122] SWC (mL / g) = (V2-V1) / M
[0123] Where V1 is the volume before expansion, V2 is the volume after expansion, and M is the weight of the sample.
[0124] 4) Solubility (WS)
[0125] WS was prepared by mixing 0.2 g SDF with 4 mL distilled water at 37 °C for 12 h, then centrifuged at 10,000 r / min for 10 min, and the supernatant was collected, dried at 105 °C, and weighed.
[0126] WS(%)=M1 / M2×100%
[0127] Where M1 is the weight of the supernatant after drying and M2 is the weight of the sample.
[0128] SDF swells in the upper digestive tract to form a gel network structure. In the large intestine, SDF absorbs water and swells to increase viscosity and soften feces, providing a lubricant for defecation. This helps prevent large intestine diseases such as constipation, diverticulitis, and colon cancer. As shown in Table 10, the swelling power of F-SDF is significantly higher than that of U-SDF and A-SDF. The solubility of F-SDF is significantly higher than that of U-SDF and A-SDF (p<0.05). This may be related to the lower molecular weight of F-SDF.
[0129] 3. Functional characteristics
[0130] 1) Cholesterol Absorption Capacity (CAC)
[0131] Fresh egg yolk was diluted with 9 volumes of distilled water and homogenized into an emulsion. 0.20 g of SDF was mixed with 10 mL of the diluted egg yolk emulsion in a 50 mL centrifuge tube. The mixture was shaken at 180 rpm for 12 h in a shaker at 37 °C, and the mixture was centrifuged at 10,000 × g for 10 min. The cholesterol content was measured with the supernatant according to the o-phthalaldehyde method, and the cholesterol adsorption capacity was expressed as milligrams of cholesterol absorbed per gram of sample.
[0132] CAC(g / g)=(m1-m2) / M
[0133] Where m1 is the weight before absorption, m2 is the weight after absorption, and M is the weight of the sample.
[0134] Cholesterol is often one of the main causes of cardiovascular disease, and highly viscous SDF can be used as an effective drug for hypercholesterolemia. In a clinical trial of patients with hypercholesterolemia, it was found that the high molecular weight and water holding capacity of SDF can increase the viscosity of digestive juices and are related to lowering blood cholesterol levels. Excretion of excess bile acids / salts is used as an explanation for the mechanism by which SDF lowers cholesterol. As can be seen from Table 10, F-SDF has the highest adsorption capacity for cholesterol at pH = 2, while A-SDF has a higher cholesterol adsorption capacity at pH = 7. A-SDF has a significantly higher adsorption capacity for cholesterol than U-SDF and F-SDF at pH = 7.
[0135] 2) DPPH free radical scavenging activity
[0136] Prepare 1 mg / mL SDF solution, mix 2 ml sample with 2 ml 0.2 mmol LDPPH solution or 95% ethanol, store in the dark for 30 min, and measure the absorbance at 517 nm using a spectrophotometer. All experiments were measured in triplicate.
[0137]
[0138] Where A0 is the absorbance of the control group (2 mL 95% ethanol instead of the sample), A1 is the absorbance of the sample (2 mL sample and 2 mL DPPH), and A2 is the absorbance of the DPPH solution replaced by 95% ethanol under the same conditions as A1.
[0139] As shown in Table 10, the DPPH free radical scavenging rate of F-SDF was significantly higher than that of A-SDF and U-SDF (p<0.05), which indicated that the composite fermentation of A. niger + cellulase could improve the antioxidant activity of SDF.
[0140] Table 10. Functional properties of different dietary fibers
[0141]
[0142] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A modification method for increasing soluble dietary fiber in corn stalks, characterized in that The following steps are involved: (1) Dry the corn stalks and crush them into 20-30 meshes using a crusher; (2) placing the crushed corn stalks in an autoclave, and then adding NaOH and water for high pressure treatment; (3) After the high pressure treatment, the corn stalks are cooled, treated with H2O2, and air-dried to obtain corn stalks treated with alkaline high pressure oxidation; (4) adding Aspergillus niger spore liquid and cellulase to the corn stover after alkaline high pressure oxidation treatment for bacteria + enzyme combined fermentation; (5) obtaining soluble dietary fiber from the fermentation broth obtained in step (4) by an enzyme-gravimetric method; In the step (2), the amount of NaOH added is 8% based on the weight of the crushed corn stalks; In step (2), the liquid-to-solid ratio of the high pressure treatment is 2:1, the high pressure treatment temperature is 121° C., the high pressure treatment pressure is 0.1 MPa, and the time is 40 min; In the step (3), the amount of H2O2 added is 6% based on the volume of the system obtained after the high pressure treatment; In the step (4), the Aspergillus niger spore solution is added in a ratio of 1:1 (w:v), wherein the amount of Aspergillus niger added is 1×10 7 CFU / mL, the amount of cellulase added was 10 FPU / g, the final liquid-solid ratio was 2:1, the pH value was 5.5, and the culture was carried out at 30°C for 5 days.
2. The method for improving soluble dietary fiber in corn stalks according to claim 1, characterized in that: The operation method of the enzyme-gravimetric method in step (5) is as follows: 0.5 g of the sample is added to 5 mL of acetic acid-sodium acetate buffer, and then the sample is added to an α-amylase solution, a protease solution and an amyloamylase solution in sequence, each at 60° C. for 30 min. The final enzymatic hydrolyzate is filtered, and the filtrate is precipitated with 95% ethanol. The precipitate is centrifuged at 10,000 × g for 10 min and dried at 65° C.
Citation Information
Patent Citations
Method for converting corn straw into reducing sugar and dietary fibers
CN111518855A
Method lfor preparing soluble dietary fiber from corn hull
US20030003216A1